2020
DOI: 10.1101/2020.07.02.182832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIF-stabilization prevents delayed fracture healing

Abstract: AbstractThe initial phase of fracture healing decides on success of bone regeneration and is characterized by an inflammatory milieu and low oxygen tension (hypoxia). Negative interference with or prolongation of this fine-tuned initiation phase will ultimately lead to a delayed or incomplete healing such as non-unions which then requires an effective and gentle therapeutic intervention. Common reasons include a dysregulated immune response, immunosuppression or a failure in ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…In addition, pro-inflammatory processes were more pronounced, which is in accordance with current findings in a mouse-osteotomy model revealing the activation of, for example, C-X-C motif chemokine ligand 3 (Cxcl3) or metallothionein 3 (Mt3) expression at day 3 after application of DFO in the fracture gap. (20) We did not expect a strong upregulation of osteogenic markers or changes in the SFBCs, which normally require longer treatment periods. (29) Nevertheless, there are many ways to foster the current approach.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, pro-inflammatory processes were more pronounced, which is in accordance with current findings in a mouse-osteotomy model revealing the activation of, for example, C-X-C motif chemokine ligand 3 (Cxcl3) or metallothionein 3 (Mt3) expression at day 3 after application of DFO in the fracture gap. (20) We did not expect a strong upregulation of osteogenic markers or changes in the SFBCs, which normally require longer treatment periods. (29) Nevertheless, there are many ways to foster the current approach.…”
Section: Discussionmentioning
confidence: 89%
“…DFO is an iron chelator, which inhibits prolylhydroxylases to chemically stabilize HIF and is a well-known osteoinductive substance. (20) After co-cultivation for 48 hours and supplementation of DFO, we found that DFO triggered the expression of osteogenic, angiogenic, and hypoxia-related genes in the in vitro FH with barely any effect on the SFBCs (Fig. 5B).…”
Section: Dfo Treatment Intensifies Pro-angiogenic Processesmentioning
confidence: 86%